Penanganan Nyeri Pascabedah Menggunakan Ketamin Dosis Rendah - Hutagalung, Yosafat F.; Tambajong, Harold; Laihad, Mordekhai L. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: Postoperative pain is a pain experienced by a patient after undergoing a surgical procedure. Postoperative pain management is an important aspect of anesthetic care. One of the recommended drugs in the management of postoperative pain is ketamine. Ketamine is a non-competitive NMDA antagonist that has been used as an analgesic for the last 3 decades. The purpose of this study was to determine how postoperative pain management using low doses of ketamine. The research method used in this study is literature review by searching data using three databases, namely Pubmed, ClinicalKey and Google Scholar. The keywords used were postoperative pain AND low dose ketamine. The results of the literature review showed that the use of low-dose ketamine resulted in lower pain scores at 1-12 hours post surgery. Low doses of ketamine also significantly reduced the mean time to administer the first postoperative analgesic and did not cause serious side effects to patients. In conclusion, low-dose ketamine has been shown to be effective in the management of acute postoperative pain by recommending a one-time IV bolus dose with a subanesthetic dose (0.35 mg / kg). The usage of low doses of ketamine causes mild side effects and safe to use for post-surgical analgesics.Key words: postoperative pain, low dose ketamine, pain score, analgesicÂ Â Abstrak: Nyeri pascabedah merupakan nyeri yang dialami seorang pasien setelah menjalani prosedur bedah. Penanganan nyeri pascabedah merupakan aspek yang penting dalam perawatan anestesi. Salah satu obat pilihan dalam penanganan nyeri pascabedah adalah ketamin. Ketamin merupakan antagonis NMDA non kompetitif yang telah digunakan sebagai analgesic selama 3 dekade terakhir. Tujuan penelitian ini adalah untuk mengetahui bagaimana penanganan nyeri pascabedah menggunakan ketamin dosis rendah. Metode penelitian yang digunakan pada penelitian ini adalahÂ literature review dengan pencarian data menggunakan tiga database yaitu Pubmed, ClinicalKey dan Google Scholar. Kata kunci yang digunakan yaitu nyeri pascabedah AND ketamin dosis rendah. Hasil dari penelitian literature review menunjukkan penggunaan ketamin dosis rendah menghasilkan skor nyeri yang lebih rendah pada 1-12 jam pasca bedah. Ketamin dosis rendah juga menurunkan waktu rata-rata pemberian analgesik pasca operasi pertama secara signifikan dan tidak menimbulkan efek samping yang serius kepada pasien. Sebagai simpulan, ketamin dosis rendah terbukti efektif pada penanganan nyeri pascabedah akut dengan rekomendasi dosis bolus IV 1 kali dengan dosis subanestetik (0,35 mg / kg). Penggunaan ketamin dosis rendah menimbulkan efek samping yang ringan dan dapat menghemat pemakaian analgesik pasca bedah.Kata kunci: nyeri pascabedah, ketamin dosis rendah, skor nyeri, analgesik